A Case of Significant Response to Olaparib in a Patient with Primary Peritoneal Carcinosarcoma Diagnosed by Laparoscopic Surgery. (10th August 2020) - Nagamata, Satoshi; Nakasuji, Yukiko; Yamanaka, Keitaro; Azumi, Maho; Washio, Keiichi; Shimizu, Maho; Takahashi, Ryosuke; Matsumoto, Kazuyo; Murata, Yuka; Suzuki, Kaho; Deguchi, Masashi; Yamada, Hideto; et al.
Abstract : Primary peritoneal carcinosarcomas which arise from extragenital locations are extremely rare. Carinosarcomas contain both carcinomatous and sarcomatous elements and can be mainly detected in the female genital tract. We herein report a case of primary peritoneal carcinosarcoma diagnosed by laparoscopic surgery and treated with olaparib. A 62-year-old woman referred to our hospital due to abdominal distension. From imaging findings, we suspected advanced primary peritoneal carcinoma, and laparoscopic surgery was thereafter performed. The pathological diagnosis was carcinosarcoma, and the patient received chemotherapy with docetaxel and carboplatin. After three cycles of chemotherapy, the interval debulking surgery was attempted but resulted in suboptimal results. Because the bilateral ovaries were observed with a normal size and normal findings, we considered that the most likely diagnosis was primary peritoneal carcinosarcoma. After the additional chemotherapy and a 6-month observation period, the tumor relapsed. The patient received chemotherapy again, and the peritoneal carcinosarcoma was judged to be a platinum-sensitive tumor. Oral administration of olaparib was thus initiated. Although a dose reduction was needed due to anemia, olaparib was effective, and the patient could continue the drug for another 7 months. This is the first report of primary peritoneal carcinosarcoma treated with olaparib and shows that it could be a treatment option for platinum-sensitive tumors.